1997
DOI: 10.1007/bf02439334
|View full text |Cite
|
Sign up to set email alerts
|

Optical alignment of organic dopants in a solid gel matrix: dispersed and grafted rhodamine B molecules

Abstract: Abstract. We study herein the rotational mobility of organic dye molecules and their ability to align on a strong optical electric field when they are encaged in the pores of an inorganic silica xerogel matrix. We compare the case of dye molecules simply dispersed in the pores of the gel--and possibly held by hydrogen bonds--to the case of molecules chemically grafted on the inner surface of these pores through covalent bonds. The study is led on hybrid silicon-zirconium based inorganic matrices doped with org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…[291] It was shown that the precuring and poling temperature impacts the nonlinear optical responses due to modification of the cross-linking. [155,156,292] An excessive cross-linking would decrease the mobility of the dyes and consequently lower the poling efficiency. This depends also in the rotational capacity of the dyes.…”
Section: Q10mentioning
confidence: 99%
See 1 more Smart Citation
“…[291] It was shown that the precuring and poling temperature impacts the nonlinear optical responses due to modification of the cross-linking. [155,156,292] An excessive cross-linking would decrease the mobility of the dyes and consequently lower the poling efficiency. This depends also in the rotational capacity of the dyes.…”
Section: Q10mentioning
confidence: 99%
“…. ) via weak (Class I hybrid) [31] or strong (Class II hybrid) chemical interactions [151][152][153][154][155][156][157][158][159][160][161][162][163][164][165] is the main approach to achieve robust and functional photochromic-based devices that could be easily handled and integrated in solid materials. Many photochromic organic molecules have been entrapped in ORMOSIL (Organically Modified Silanes) hybrid matrices.…”
Section: Organic Photochromism In Hybridsmentioning
confidence: 99%
“…Additionally, the preparation of hybrid fluorescent pigments using the sol-gel method was proposed by Hofacker and Schottner [12], enlarging the possible applications for this material. Few works using rhodamine in grafting reactions have been reported, where silica based monoliths and films were obtained [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…1 The organic/inorganic hybrids are classified based on their mixing and connections: 2 (1) dispersion type, (2) interpenetrating type, and (3) molecular hybrid type. In hybrids of (1) the dispersion type, inorganic materials are dispersed in organic polymers, [3][4][5] or organic materials are dispersed in inorganic polymers. 6 Because the organic and inorganic components in this type of hybrid are phase-separated, a homogeneous mixture of organic/inorganic hybrid materials is prepared by applying molecular interactions between organic and inorganic components such as hydrogen bonding and -interactions.…”
mentioning
confidence: 99%